DIFFERENCE BETWEEN VOISE OF VERB IN ENGLISH AND UZBEK LANGUAGE - Axmatova Madina; Muhammadiyev Aziz Shavkatovich (Лучшие интеллектуальные исследования, 2024)
This article explores the distinctions in verb voice between English and Uzbek languages. It outlines the two voices in English (active and passive) and the three voices in Uzbek (active, causative, and reflexive). The active voice in both languages involves the subject directly performing the action. However, English expresses passive voice using "be" and the past participle, while Uzbek employs a causative voice to indicate that the subject causes someone else to perform the action. Additionally, Uzbek employs a reflexive voice to indicate that the subject performs an action on itself. The annotation provides a concise summary of the main points discussed in the text, highlighting the key differences between the two languages in terms of verb voice.